STANDARISASI PARAMETER NON SPESIFIK SIMPLISIA RIMPANG KUNYIT (Curcumae Domestica Rizhoma) DAN TEMULAWAK (Curcuma xanthorrhiza Roxb.) DI KABUPATEN PONOROGO - yaya sulthon aziz (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Simplicia of turmeric and ginger is widely cultivated and developed by local farmers. Making these simplicia often does not meet the quality requirements because the process is still traditional and there are no guidelines used, there are still many raw materials for turmeric and ginger. The farmers of Ponorogo Regency cannot penetrate the traditional drug factory market. Objective: To determine the quality of turmeric and curcuma simplicia in Ponorogo. Method: Simplicia samples originating from Slahung village, Slahung sub-district, Ponrogo Regency were taken by purposive sampling. Quality testing is carried out according to FHI Issue I of 2008 and Republic of Indonesia BPOM Regulation Number 12 of 2014. Results: In testing turmeric rhizomes, referring to BPOM Number 12 of 2014 on water content testing, AKK test and ALT test meet the requirements. In the first edition of FHI parameters in 2008 did not meet the requirements of the curcuminoid test parameters, total ash content test, acid insoluble ash test, ethanol soluble extract test, water soluble juice test, but at the test of essential oil content and shrinkage test drying meets the requirements. None of the ginger rhizomes meet the quality test requirements. Conclusions and suggestions: Simplicia of turmeric and ginger in Ponorogo Regency has not met the quality requirements of traditional medicine and it is expected that farmers improve in the planting, harvesting and post-harvesting processes.